Synthesis of substituted 6-cyclopropylpurine bases and nucleosides by cross-coupling reactions or cyclopropanations - Kuchař, Martin; Pohl, Radek; Klepetářová, Blanka; Votruba, Ivan; Hocek, Michal (Organic & biomolecular chemistry, 2008)
Synthesis of novel purine bases and nucleosides bearing unsubstituted or substituted cyclopropyl rings in position 6 is reported. Unsubstituted 6-cyclopropylpurines were efficiently prepared by cross-coupling reactions of 6-chloropurines with cyclopropylzinc chloride. 6-Vinylpurines underwent Cu-mediated cyclopropanations with ethyl diazoacetate to give 6-[(ethoxycarbonyl)cyclopropyl]purines that were further transformed to carboxylic acids, amides and alcohols. 6-Cyclopropylpurine ribonucleoside exerted a significant cytostatic effect while all substituted derivatives were inactive.
Keywords: financování organizované; Animals; myši; Cyclopropanes; proliferace buněk; Humans; Cell Proliferation; lidé; Financing, Organized; zvířata; Crystallography, X-Ray; Mice; Purine Nucleosides; Cell Line, Tumor; nádorové buněčné linie; cyklopropany; purinové nukleosidy; krystalografie rentgenová